MOTIVACIÓN DEL PERSONAL ADMINISTRATIVO EN EL GAD DEL CANTÓN VINCES - Bravo Haramuniz, Lisseth Rupzabala (2019)
he present case study focuses on the motivation of the administrative staff of the Municipal Autonomous Decentralized Government of the Canton of Vinces, dedicated to the service of the Vinceña community, with the realization of works, agreements with the purpose of improving the living conditions of the various dwellings of the neighborhoods and citadels, the person in charge during this mandate is the Eco. Cristian Raúl Villasagua Santana